104k views
3 votes
Select the simplification that accurately explains the following statement.

Select the simplification that accurately explains the following statement.-example-1
User DokiCRO
by
4.9k points

1 Answer

3 votes

Answer:

D

Explanation:

1. Use property of exponents:


(a^b)^c=a^b\cdot ... \cdot a^b\ [\text{ take }c \text{ times } a^b]

Hence


(7^{(1)/(3)})^3=7^{(1)/(3)}\cdot 7^{(1)/(3)}\cdot 7^{(1)/(3)}

2. Use multiplication property of exponents:


a^b\cdot a^c=a^(b+c)

Thus,


7^{(1)/(3)}\cdot 7^{(1)/(3)}\cdot 7^{(1)/(3)}=7^{(1)/(3)+(1)/(3)+(1)/(3)}

3. Since


(1)/(3)+(1)/(3)+(1)/(3)=(3)/(3)=1,

we have that


7^{(1)/(3)+(1)/(3)+(1)/(3)}=7^1=7

User Spen D
by
6.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.